The Effect of Compensation and Work Motivation on Work Discipline at the Corruption Eradication Commission - Ariromas, Perigia; Wahyuningtyas, Ratri (Journal Research of Social Science, Economics, and Management, 2026)
This research aims to analyze the effect of compensation and work motivation on employees’ work discipline at KPK, both partially and simultaneously, as well as to describe the conditions of the three variables. This quantitative survey collected primary data from 315 KPK employees through questionnaires and analyzed them using PLS-SEM to examine variable relationships and assess model adequacy. The results indicate that compensation falls within the “good” category, while work motivation and work discipline fall within the “very high” category. The structural model testing shows that work motivation has a positive and significant effect on work discipline ( ; ) with a large effect size. Compensation also has a positive and significant effect ( ; ), although with a small effect size. The value of 0.414 indicates moderate explanatory power, meaning that 41.4% of the variance in work discipline can be explained by compensation and work motivation. This study concludes that compensation and work motivation have a positive and significant effect on employees’ work discipline at KPK, with work motivation serving as the primary determinant. The practical implications highlight the need for HR policies that emphasize both fair compensation and enhanced work motivation, achieved through competency development, career management, supportive environments, and strong leadership. Additionally, the study suggests future research should include more variables and comprehensive designs to better understand work discipline in the public sector.